Robotics: Science and Systems XI 2015
DOI: 10.15607/rss.2015.xi.037
|View full text |Cite
|
Sign up to set email alerts
|

Get Out of My Lab: Large-scale, Real-Time Visual-Inertial Localization

Abstract: Abstract-Accurately estimating a robot's pose relative to a global scene model and precisely tracking the pose in real-time is a fundamental problem for navigation and obstacle avoidance tasks. Due to the computational complexity of localization against a large map and the memory consumed by the model, state-ofthe-art approaches are either limited to small workspaces or rely on a server-side system to query the global model while tracking the pose locally. The latter approaches face the problem of smoothly int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
214
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(216 citation statements)
references
References 51 publications
1
214
0
1
Order By: Relevance
“…Therefore, future work may also attempt to use visual feature tracking algorithms in order to recognise areas that have been revisited (i.e. within an animal's home range) to perform drift correction or loop closure [72][73][74]. Such a feature, known as ' Area Learning' on the Tango platform, could allow researchers to visit and 'learn' an area in advance to produce area description files that correct errors in trajectory data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future work may also attempt to use visual feature tracking algorithms in order to recognise areas that have been revisited (i.e. within an animal's home range) to perform drift correction or loop closure [72][73][74]. Such a feature, known as ' Area Learning' on the Tango platform, could allow researchers to visit and 'learn' an area in advance to produce area description files that correct errors in trajectory data.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we propose the use of a framework based on [14]. The idea is to provide a statistically consistent interface between visualinertial odometry and a mapping backend.…”
Section: A Localization and Mappingmentioning
confidence: 99%
“…[12]). The discussed localization and mapping framework provides an accurate pose estimation (see [14] for an evaluation), but the obtained bandwidth (5 Hz) is insufficient for the feedback controller for stabilizing the system. In order to overcome the above shortcoming, an EKFbased state estimator is implemented on the legged robot as presented in [17].…”
Section: B Legged State Estimationmentioning
confidence: 99%
“…In contrast to traditional structure-frommotion techniques, where features between all frames exhaustively are attempted to match, (Warren, 2015) utilizes the vocabulary-tree-based openFABMAP (Glover et al, 2012) library for loop closing. Recently (Lynen et al, 2015) demonstrated that large-scale, real-time pose estimation and tracking can be performed on mobile platforms by employing map and descriptor compression schemes together with efficient search algorithms.…”
Section: Landmark Trackingmentioning
confidence: 99%